2006
DOI: 10.1007/s10764-006-9078-4
|View full text |Cite
|
Sign up to set email alerts
|

Reconciliation and Consolation in Captive Western Gorillas

Abstract: We studied post-aggression mechanisms in a captive group of western gorillas (Apenheul Primate Park, The Netherlands) and compared them with those of wild mountain gorillas (Gorilla beringei). We found the same trend for reconciliation that wild mountain gorillas show: reconciliation occurred only between adult male-female dyads, while it was absent in the other sexage class combination. There were both solicited and nonsolicited contacts; the latter finding is in contrast with the result obtained in wild moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
64
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 41 publications
3
64
0
Order By: Relevance
“…These functions, however, have never been tested, and as the mechanisms of solicited consolation may be different from consolation; the two postconflict interactions should be considered separately. Although solicited consolation has been demonstrated in many primate species [Watts et al, 2000], a number of studies on apes have not found any evidence for it, even when consolation has been demonstrated Kutsukake & Castles, 2004;Wittig & Boesch, 2003; but see Cordoni et al, 2006;Mallavarapu et al, 2006;Palagi et al, 2004Palagi et al, , 2006. The inconsistencies in the results obtained from previous studies thus emphasize the need for further research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…These functions, however, have never been tested, and as the mechanisms of solicited consolation may be different from consolation; the two postconflict interactions should be considered separately. Although solicited consolation has been demonstrated in many primate species [Watts et al, 2000], a number of studies on apes have not found any evidence for it, even when consolation has been demonstrated Kutsukake & Castles, 2004;Wittig & Boesch, 2003; but see Cordoni et al, 2006;Mallavarapu et al, 2006;Palagi et al, 2004Palagi et al, , 2006. The inconsistencies in the results obtained from previous studies thus emphasize the need for further research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…7,10 The majority of research on post-conflict behavior has focused on reconciliation, the affiliative post-conflict interaction between former opponents, 11,12 but important post-conflict interactions may also occur between the opponents and bystanders uninvolved in the previous conflict. 13,14 In particular, a number of recent studies have demonstrated the phenomenon of post-conflict affiliation directed from a bystander to the recipient of aggression in a variety of species from primates [15][16][17][18][19][20][21][22][23][24][25] to dogs 26 and rooks. 27 This review focuses on bystander to recipient interactions and examines the variations in their patterns, which are consistent with a number of different functional explanations.…”
Section: Introductionmentioning
confidence: 99%
“…Consolation has been demonstrated convincingly only in the great apes [Pan troglodytes (2,10,(12)(13)(14)(15), Pan paniscus (16), and Gorilla gorilla (17,18)]. De Waal and Aureli (10) have speculated that consolation may reflect a level of empathy unique to humans and apes.…”
mentioning
confidence: 99%